2006
DOI: 10.2220/biomedres.27.157
|View full text |Cite
|
Sign up to set email alerts
|

Influence of prostaglandin A2 on Bax, Bcl-2 and PCNA expression in MCF-7 cells

Abstract: The effects of 20 μg/mL exogenous prostaglandin A 2 (PGA 2 ) were determined on Bax, Bcl-2 and proliferating cell nuclear antigen (PCNA) expression levels in MCF-7 cells. Flow cytometric analysis indicated a pronounced increase in the S phase and a decrease in the G 1 phase, whereas a significant increase in the DNA content preceding the G 0 /G 1 peak was also observed after 48 h of exposure to PGA 2 . Confirmation of apoptosis was determined after 12 h, 36 h and 48 h of PGA 2 exposure employing the mitosensor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 23 publications
1
3
0
Order By: Relevance
“…The Wnt/β-catenin pathway is related to the efficacy of MSCs in suppressing hepatoma and breast cancer (18,28,35). The Bcl-2, c-Myc, PCNA and survivin genes are all targets of the Wnt/β-catenin signaling pathway (36,37). In the present study, western blot analyses confirmed that the Wnt/β-catenin signaling pathway in SHZ-88 cells was blocked by PMSC-conditioned medium.…”
Section: Discussionsupporting
confidence: 76%
“…The Wnt/β-catenin pathway is related to the efficacy of MSCs in suppressing hepatoma and breast cancer (18,28,35). The Bcl-2, c-Myc, PCNA and survivin genes are all targets of the Wnt/β-catenin signaling pathway (36,37). In the present study, western blot analyses confirmed that the Wnt/β-catenin signaling pathway in SHZ-88 cells was blocked by PMSC-conditioned medium.…”
Section: Discussionsupporting
confidence: 76%
“…Wnt signaling regulates genes that are involved in cell metabolism, proliferation, cell-cycle regulation and apoptosis [30,31]. The PCNA, c-Myc, survivin and Bcl-2 genes are all targets of Wnt signaling [32,33].…”
Section: Discussionmentioning
confidence: 99%
“…27,28 The PCNA, survivin and β-Catenin genes are all targets of Wnt signaling. 29,30 Zhu et al 31 demonstrated that MSCs have an inhibitory effect on tumor proliferation by identifying that DKK-1 (dickkopf-1) which was secreted by MSCs, acts as a negative regulator of Wnt signaling pathway and is one of the molecules responsible for the inhibitory effect of MSCs on tumor. MSCs also up regulate the mRNA expression of cell-cycle negative regulator p21 and apoptosis-associated protease caspase-3, resulting in a G0/G1 phase arrest and apoptotic cell death of tumor cells.…”
Section: Discussionmentioning
confidence: 99%